An evaluation of input measures and outcomes of the extended-hours service in the general reference section of UP Diliman Main Library a basis for a development plan - Janio, Rizalyn V.; Obille, Kathleen B.; Cornago, Pia Charmaine F.; Lapuz, Elvira B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2015)
For the last five decades, the term opening hours had come to mean extending library hours beyond the traditional schedules. The study aimed to evaluate the extended-hours service of the General Reference Section of UP Diliman Main Library to describe its operation, and diagnose how the program is doing today, 15 years since it was implemented.
The study's design was descriptive. The study gathered data from both management and user perceptions. The respondents were the six staff of the extended-hours service of the General Reference Section for the focus group discussion (FGD) and the student and faculty library patrons-both day time patrons and those who avail of the extended-hours service-were asked to fill out questionnaires. The total number of respondents was 136, of which q26 are student patrons and 10 are faculty patrons. The accomplished questionnaires were organized, tabulated, and subjected to descriptive statistical methods with the use of the software Statistical Package for the for the Social Sciences (SPSS) and weighted mean were computed--the computed weighted mean were interpreted based on Likert Scale while Editing Analysis Style was utilized for the focus group discussion (FGD).
The study found that the staff members of the extended-hours if the General Reference Section of the UP Diliman Main Library have has a grapple with the following challenges: the main library has two guards at daytime, and just one at night, the numbers of staff who take care of the needs of patrons for the last 15 years have always been ideal, and discontentment with the salary that they receive for serving during extended hours. An overwhelming majority of the student and faculty library patrons of the extended-hours service feel that the said service is important but were generally dissatisfied in terms of resources, operations and environment, cognitive and affective results, meeting expectations, accomplishments, and time and money aspects.
The researcher recommends that the administration and staff of the General Reference Section of the UP Diliman Main Library consider this study's Development Plan which contains suggested strategies to help them cope with the identified challenges and issues that accompany the operations of the extended-hours service. The following aspects of the operations of the service be addressed properly and promptly as they the patrons have found these wanting: (1) The physical accessibility of the library; (2) ease and convenience in utilizing the library resources and services; (3) the helpfulness and efficiency of the staff; (4) clarity of library policies; (5) perceived cognitive benefit of utilizing the library; and (6) perceived effective benefit of utilizing the library; and (7) perceived accomplishment benefit of utilizing the library.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Academic libraries -- Reference services; Nightwork -- Philippines -- Quezon City